A Practical Approach for a Wide Range of Liver Iron Quantitation Using a Magnetic Resonance Imaging Technique. (11th December 2012) - Hou, Ping; Popat, Uday R.; Lindsay, Richard J.; Jackson, Edward F.; Choi, Haesun
Abstract : The goal of this study is to demonstrate a practical magnetic resonance imaging technique for quantifying a wide range of hepatic iron concentration (HIC) for hematologic oncology patients with transfusion iron overload in a routine clinical setting. To cover a wide range ofT 2 * values from hematologic patients, we used a dual-acquisition method with two clinically available acquisition protocols on a 1.5T MRI scanner with different ΔTEs to acquire data in two breath-holds. An in-house image postprocessing software tool was developed to generateT 2 *, iron maps, and water and fat images, when fat is presented in the liver. The resulting iron maps in DICOM format are transferred to the institutional electronic medical record system for review by radiologists. The measured liverT 2 * values for 28 patients ranged from0.56 ± 0.13 to25.0 ± 2.1 milliseconds. TheseT 2 * values corresponded to HIC values ranging from1.2 ± 0.1  mg/g to45.0 ± 10.0  mg/g (dry weight). A moderate correlation between overall serum ferritin levels andR 2 * was found with a correlation coefficient of 0.83. Repeated phantom scans confirmed that the precision of this method is better than 4% forT 2 * measurements. The dual- acquisition method also improved the ability to quantify HIC of the patients with hepatic steatosis.